Trends, costs, benefits, challenges, and prognoses for supplementary materials. (31st August 2016) - Shutler, Dave; Murray, Ashley
Abstract: Supplementary materials (SM) are a relatively new addition to published research. The volume of SM has been increasing over time for many journals, and in a few cases SM appear to be replacing appendices. We review the costs and benefits of SM to authors, reviewers, production teams, and readers. We conclude that SM can have value but that they place additional demands on all participants. Given the difficulty of recruiting reviewers for journal submissions and the added effort required by all participants, this may lead to incomplete vetting that may undermine the reliability of SM in some instances.